The Effect of Current Ratio, Debt to Asset Ratio, and Debt to Equity Ratio on Return on Assets in Pharmaceutical Companies on the Indonesian Stock Exchange, Period 2015–2024 - Rahmawati, Rika; Herlinawati, Erna; Suryaningprang, Andre (Asosiasi Ahli Administrasi Indonesia, 2025)
The pharmaceutical industry is an influential industrial sector in the Indonesian economy. However, by the end of 2024, almost all state-owned pharmaceutical companies experienced a decline in profits due to various problems such as the spread of vaccines and medicines due to the end of the Covid-19 pandemic, to serious problems such as accumulating debt and impacting the company's operational costs. Therefore, the author is interested in conducting research that impacts company profitability, namely the effect of the Current Ratio, Debt to Asset Ratio, and Debt to Equity Ratio on Return on Assets in the pharmaceutical industry listed on the Indonesian Stock Exchange for the period 2015-2024. Data were taken from annual report data and the sample used was 40 from four pharmaceutical industries, namely PT. Indofarma Tbk, PT. Kimia Farma Tbk, PT. Phapros Tbk and PT. Pyridam Farma Tbk. The data were analyzed using panel data regression and processed using Eviews 12 software. The results of partial hypothesis testing showed that the Current Ratio and Debt to Equity Ratio had no significant effect on Return on Assets, while the Debt to Asset Ratio had a significant effect on Return on Assets. Simultaneously, the variables Current Ratio, Debt to Asset Ratio and Debt to Equity Ratio had a significant effect on Return on Assets of pharmaceutical companies listed on the Indonesia Stock Exchange.